Fueling the fire: Examining identity centrality, affective interpersonal commitment and gender as drivers of entrepreneurial passion - Murnieks, Charles Y.; Cardon, Melissa S.; Haynie, J. Michael (Journal of Business Venturing, 2020)
Research on passion is burgeoning in the entrepreneurial literature, yet we still know little about what factors drive entrepreneurial passion. Recognizing the socially embedded nature of entrepreneurship, we examine identity-related social forces that may fuel the fire of entrepreneurial passion. Employing a lagged design that controls for known antecedents, we find different pathways driving harmonious versus obsessive entrepreneurial passion. We find that harmonious entrepreneurial passion is fueled by entrepreneurial identity centrality whereas obsessive entrepreneurial passion is fueled by affective interpersonal commitment. Interestingly, gender moderates both these relationships.